The Effect of High-Fat Diet and Exercise Intervention on the TNF-α Level in Rat Spleen - Feng, Lin; Huang, Feiyun; Ma, Yinan; Tang, Jialing (Frontiers in Immunology, 2021)
High-fat diet (HFD) consumption can trigger chronic inflammation in some tissues. However, it remains unclear if HFD induces chronic inflammation in the spleen. This investigation aims to address the effect of HFD consumption and exercise intervention on the level of tumor necrosis factor alpha (TNF-α) in the spleen. Rats were subjected to HFD feeding or/and moderate-intensity treadmill running. The TNF-α levels in plasma and spleen was detected by ELISA. The mass and total cell numbers of the spleen were measured. In addition, the expression of TNF-α and its relevant gene mRNAs in macrophages from the spleen were analyzed by qRT-PCR. We found that HFD consumption did not significantly affect the mass and total cell numbers of the spleen. However, HDF consumption significantly increased splenic TNF-α level, the expression of TNF-α, toll-like receptor 4, and nuclear factor κB p65 mRNAs. In contrast, the expression of nicotinic acetylcholine receptor alpha 7 subunit mRNA in macrophages was down-regulated. Additionally, exercise abolished the increase in splenic TNF-α level as well as the abnormal expression of TNF-α and related gene mRNAs in macrophages in HFD fed rats. In conclusion, our results reveal that HFD consumption increases TNF-α level in the spleen, which is along with up-regulation of the expression of TLR4 and NF-κB mRNAs as well as down-regulation of the expression of α7nAChR mRNA in splenic macrophages in rats. Exercise abolished detrimental effects of HFD on TNF-α level in the spleen and prevented abnormal expression of these genes in the macrophages from rat spleen.